AN EXAMINATION OF INTERFAITH MARRIAGE FROM THE PERSPECTIVE OF ISLAMIC THEOLOGY - Rangga Iskandar Dinata; Kartika, Resti Okvani; Awaluddin, Raisa Zuhra Salsabila; Ahmad Arifi (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2024)
Marriage is a physical and mental bond between two people who live a family life. Interfaith marriage is a problem that occurs in society. This type of research is qualitative using the library study method (Library Research) by collecting data obtained from various literatures so that it can be selected and correlated with the research title and analyzed using a theological approach to obtain conclusions. The purpose of this study is to determine the analysis of interfaith marriages in the perspective of a theological approach. The results of this study are two conclusions; first, Q.S Al-Baqarah: 221 is a strict prohibition of interfaith marriage because it has a close relationship to divinity and gives birth to offspring that have an influence on education in the development of Islam. Second, Q.S Al- Maidah: 5 allows interfaith marriage on the condition that a Muslim marries a woman of the book who maintains her honor (muhshanat) and prohibits interfaith marriage for a Muslim woman who marries a member of the book (non-Muslim) or a disbeliever.